RNA-Based Vaccines in Cancer Immunotherapy - Megan A. McNamara; Smita K. Nair; Eda K. Holl (Journal of Immunology Research)
RNA vaccines traditionally consist of messenger RNA synthesized by in vitro transcription using a bacteriophage RNA polymerase and template DNA that encodes the antigen(s) of interest. Once administered and internalized by host cells, the mRNA transcripts are translated directly in the cytoplasm and then the resulting antigens are presented to antigen presenting cells to stimulate an immune response. Alternatively, dendritic cells can be loaded with either tumor associated antigen mRNA or total tumor RNA and delivered to the host to elicit a specific immune response. In this review, we will explain why RNA vaccines represent an attractive platform for cancer immunotherapy, discuss modifications to RNA structure that have been developed to optimize mRNA vaccine stability and translational efficiency, and describe strategies for nonviral delivery of mRNA vaccines, highlighting key preclinical and clinical data related to cancer immunotherapy.